Efficient cocured scarf repair of composite structures through rheology modeling - David B. Bender (Taylor & Francis Group, 2021)
To address the need for increased efficiency and high-quality in-field repair of composite structures, a vacuum bag only (VBO) semi-preg was produced, modeled, and evaluated against a conventional resin and format commonly used for repairs. The semi-preg featured a vinyl hybrid resin formulated for rapid processing with a discontinuous distribution of resin on the fiber bed. The format imparted high through-thickness air permeability relative to conventional out-of-autoclave (OoA) prepregs by virtue of abundant air evacuation pathways with short breathe-out distances. A model was developed to describe the rheological behavior of the resin, and then flow number analysis was employed to assess model accuracy and to guide the design of efficient cure cycles. A custom-built scarfed repair tool featuring an in situ observation window was employed to analyze the resin flow and cure process during a scarf repair. Microstructural quality and interlaminar shear strength were compared across the epoxy/vinyl hybrid and conventional/semi-preg panels. The results demonstrated that fast-cure resins can be used in conjunction with flow number analysis and semi-preg formats to design efficient VBO cure cycles that consistently yield patch repairs with low defect contents in repair environments.